The Demography Of Less Developed Region: Population Decline In Pomurje And Population Ageing - Malačič, Janez (Anali PAZU HD, 2022)
Pomurska region has been the most stable region in Slovenia since the early 1950s due to geopolitical reasons. Therefore, it is very good case for regional demographic study. The population of the region has declined by around 11 % since the middle of the 20th century while the population of Slovenia has increased by around 37 % in the same period. However, general population development has been surprisingly similar in both units studied in the paper. Modern demographic regime has prevailed in Pomurska region and Slovenia since the 1950s. Fertility differences have been relatively small between the region and the state. More important have been mortality and migration differences which have caused most of the differences in the population growth. Pomurska region and Slovenia have experienced profound population ageing in spite of the fact that the process has been stronger in the region. The population decline in the region has not destabilized yet the most basic relations between age groups of children, working adults and older population.